Binder combination, electrode plate and solid-state battery

By using a combination of polymers with sulfonate groups and binders with inorganic substances in all-solid state batteries, physical crosslinking points are formed, and the problem of poor stability of sulfide electrolytes and polar binder materials is solved, and the problem of improved stability of sulfide electrolytes and polar binder materials is improved. The adhesion of the electrode sheet and the overall performance of the battery.

CN119193043APending Publication Date: 2024-12-27ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352909.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In all-solid state batteries, the stability of the sulfide electrolyte and polar binder materials is poor, resulting in insufficient bonding strength, and easy to cause powder loss and cracking of the electrode sheet, affecting the performance and reliability of the battery.

Method used

Using a bonding agent combination, including polymers and inorganic substances with sulfonate groups, the bonding properties are improved through physical crosslinking points between sulfonate groups and the dispersion of conductive agents to form a more effective Conductive network.

Benefits of technology

It improves the adhesion and mechanical strength of the electrode sheet, improves the reliability and electrochemical performance of the battery, and reduces the powder loss and cracking of the electrode sheet during processing or use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005062815690000131
    Figure BDA0005062815690000131
  • Figure BDA0005062815690000141
    Figure BDA0005062815690000141
  • Figure BDA0005062815690000142
    Figure BDA0005062815690000142
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a binder combination, an electrode plate and a solid-state battery. A binder combination comprises a first binder and a second binder, the first binder comprising a polymer with a first characteristic group; the second binder comprises an inorganic substance with a second characteristic group; wherein the first characteristic group and the second characteristic group respectively comprise a sulfonate group. The electrode pole piece comprises the provided binder combination. According to the invention, the cohesiveness of the electrode pole piece can be improved, the phenomena of powder falling and cracking of the electrode pole piece in the processing or using process caused by low bonding strength can be reduced or avoided, and the improvement of the overall performance and reliability of the battery is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a binder combination, an electrode plate and a solid-state battery. Background Art

[0002] All-solid-state batteries use solid electrolytes to replace traditional separators and electrolytes, which not only improves safety but also places higher requirements on the ionic conductivity of the electrolyte. At present, the main solid electrolytes studied in solid-state batteries include polymers, oxides, sulfides and halides. Among them, sulfide electrolytes have become the focus of research due to their excellent ion conductivity and easy processing.

[0003] In traditional liquid batteries, polar solvents and binders with polar groups are usually used. These polar materials can effectively provide the required bonding strength to meet the processing and use requirements of electrode plates. However, in all-solid-state batteries, the stability of sulfide electrolytes and polar binder materials is poor and chemical reactions are prone to occur. Therefore, non-polar or weakly polar materials need to be selected as alternatives. However, this change in material selection has brought new problems. The interaction between non-polar or weakly polar binder materials and other components in the electrode plates is weak, resulting in insufficient bonding strength. This problem of low bonding strength may cause powder loss and cracking of the electrode plates during processing or use, affecting the overall performance and reliability of the battery.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a binder combination, an electrode plate and a solid-state battery, which can improve the adhesion of the electrode plate, reduce or avoid the powder loss and cracking of the electrode plate during processing or use due to low bonding strength, and help improve the overall performance and reliability of the battery.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] According to one aspect of the present application, an embodiment of the present application provides a binder combination, the binder combination comprising:

[0008] a first binder, the first binder comprising a polymer having a first characteristic group; and

[0009] A second binder, wherein the second binder includes an inorganic substance having a second characteristic group;

[0010] Wherein, the first characteristic group and the second characteristic group respectively include a sulfonate group.

[0011] In addition, the adhesive combination according to the present application may also have the following additional technical features:

[0012] In some embodiments, the polymer having a first characteristic group comprises a sulfonated polymer.

[0013] In some embodiments, the first characteristic group includes a terminal group -SO3M, wherein the M includes a metal element.

[0014] In some embodiments, M includes at least one of Li, Na, Mg, Al, Ca, K, Pd or Ba.

[0015] In some embodiments, the sulfonation degree of the sulfonated polymer is 0.01 to 1 mol / kg.

[0016] In some embodiments, the sulfonation degree of the sulfonated polymer is 0.1 to 0.5 mol / kg.

[0017] In some embodiments, the polymer in the polymer with the first characteristic group includes at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyether sulfone, polyether ketone, polyarylether, polyimide, polyester, ethylene propylene rubber, butyl rubber, fluororubber, styrene butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polystyrene-poly(ethylene-butylene)-polystyrene block copolymer or polystyrene-polybutadiene-polystyrene triblock copolymer.

[0018] In some embodiments, the inorganic substance having the second characteristic group includes a sulfonated carbon material.

[0019] In some embodiments, the sulfonated carbon material includes at least one of sulfonated graphite, sulfonated graphene, sulfonated carbon nanotubes or sulfonated carbon fibers.

[0020] In some embodiments, the mass ratio of the first binder to the second binder is (80-99):(1-20).

[0021] According to another aspect of the present application, an embodiment of the present application provides an electrode plate, the electrode plate comprising a current collector and an electrode film layer disposed on a surface of the current collector;

[0022] The electrode film layer comprises an active material, a solid electrolyte, a conductive agent and the binder combination as described above.

[0023] In some of the embodiments, the solid electrolyte comprises a sulfide electrolyte.

[0024] In some embodiments, the sulfide electrolyte includes at least one of LGPS, LSPS, LPS or Li6PS5X; wherein X is selected from at least one of Cl, Br or I.

[0025] In some embodiments, the electrode plate is a positive electrode plate, and the active material includes at least one of a lithium-containing transition metal oxide containing a nano-coating layer, a lithium-containing transition metal sulfide, elemental sulfur, or a sulfur-carbon mixture.

[0026] In some embodiments, the active material includes at least one of lithium-containing transition metal composite oxides, elemental sulfur, and sulfur-carbon mixtures such as LMO (lithium manganese oxide), LCO (lithium cobalt oxide), NMC (lithium nickel manganese cobalt oxide), NCA (lithium nickel cobalt aluminum oxide), LNCO (lithium nickel cobalt oxide), olivine-type compounds (LiMePO4, Me = one or more of Fe, Co, Ni, Mn) containing a nano-coating layer.

[0027] In some embodiments, the material of the nano-coating layer is at least one selected from Li3PO4, Al2O3, LiNbO3, LiAlO2, Li3BO3, Li2OZrO2, MgO, HfO2, Li2SiO3, B2O3, Li2O, Nb2O5, P2O5, SiO2, Sc2O3, TiO2 or ZrO2.

[0028] In some embodiments, the electrode plate is a negative electrode plate, and the active material includes a carbon-based material and / or a silicon-based material.

[0029] In some embodiments, the active material includes one or more of graphite, silicon, silicon-oxygen, silicon-carbon, graphene, soft carbon or hard carbon.

[0030] In some embodiments, the conductive agent includes at least one of conductive graphite, conductive carbon black, vapor-grown carbon fiber, carbon nanotubes, or conductive graphene.

[0031] In some embodiments, the mass ratio of the active material, the solid electrolyte, the conductive agent and the binder is (50-90): (10-30): (1-5): (1-10).

[0032] In some embodiments, the method for preparing the electrode sheet includes:

[0033] The binder combination is mixed with a solvent to obtain a glue solution, and then the glue solution is mixed with an active material, a solid electrolyte, and a conductive agent to obtain a pole piece slurry. The pole piece slurry is coated on a current collector, and after heating and drying, an electrode pole piece is obtained.

[0034] In some embodiments, the solvent includes aliphatic hydrocarbons, aromatic hydrocarbons, esters, ethers, and alcohol solvents, including aliphatic hydrocarbon solvents such as pentane, hexane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, and tridecane; cycloalkane solvents such as cyclohexane and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, p-xylene, mesitylene, ethylbenzene, and tert-butylbenzene; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, and benzyl acetate; ether solvents such as dibutyl ether, diamyl ether, anisole, diethylene glycol diethyl ether, and cyclopentyl methyl ether; and alcohol solvents such as methanol, ethanol, isopropanol, and benzyl alcohol.

[0035] In some embodiments, the drying heating temperature is 60-100° C. and the time is 10-20 hours.

[0036] According to another aspect of the present application, an embodiment of the present application provides a solid-state battery, which includes the electrode plate as described above.

[0037] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0038] In an embodiment of the present application, the provided binder combination includes a first binder and a second binder, wherein the first binder includes a polymer with a first characteristic group, and the second binder includes an inorganic substance with a second characteristic group, and the first characteristic group and the second characteristic group respectively include a sulfonate group. Thus, the inorganic substance with the second characteristic group is used as a bonding active site to form a physical crosslinking point with the polymer with the first characteristic group, that is, the first binder and the second binder can interact with each other through the sulfonate group to form a physical crosslinking point, which can alleviate the problem of low bonding strength between electrolytes such as sulfide solid electrolytes and non- / weakly polar binders, and improve the bonding between the components in the electrode plate. In addition, using an inorganic substance with a second characteristic group as a bonding active site can improve the dispersibility of the binder combination and the conductive agent, and can also improve the electronic conductivity, forming a more effective conductive network, which is conducive to improving the rate performance of the electrode plate, and then it is conducive to improving the reliability and electrochemical performance of the battery containing the electrode plate.

[0039] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0040] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0041] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0042] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0043] As analyzed in the background technology, in all-solid-state batteries, the stability of sulfide electrolytes and polar binder materials is poor and chemical reactions are prone to occur. The use of non-polar or weakly polar binder materials will result in weak interactions with other components in the electrode plates, resulting in insufficient bonding strength. Therefore, it is urgent to provide a new type of binder to improve the problem of weak interactions between the binder material and other components, resulting in insufficient bonding strength, and thus avoid the problem of powder loss and cracking of the electrode plates during processing or use due to this low bonding strength problem, which may affect the overall performance and reliability of the battery.

[0044] In view of this, the inventors of the present application have improved the binder in the coated electrode sheet from the perspective of improving and combining different binders, and provided a binder combination with strong bonding properties that can be used in electrode sheets, and provided electrode sheets and solid-state batteries using the binder combination, so as to achieve the purpose of increasing the adhesion (or bonding force) between the binder and each component, thereby improving the reliability and electrochemical performance of the battery. The present application is described in detail below.

[0045] [Binder combination]

[0046] In some embodiments, a binder combination is provided, the binder combination comprising:

[0047] A first binder, the first binder comprising a polymer having a first characteristic group; and

[0048] A second binder, the second binder comprising an inorganic substance having a second characteristic group;

[0049] Wherein, the first characteristic group and the second characteristic group respectively include sulfonate (-SO3 - ) group.

[0050] In the present application, the provided binder combination may be mainly composed of a first binder and a second binder, wherein the first binder and the second binder both have characteristic groups (also referred to as functional groups), for example, the characteristic groups may include sulfonate (-SO3 - Thus, the first binder may be a binder having a sulfonate group (-SO3 - ) group, the second binder may be a polymer with a sulfonate group (-SO3 - ) group, by combining the first binder and the second binder, the interaction between the non-polar or weakly polar material and other components of the electrode plate can be effectively alleviated, resulting in insufficient bonding strength, and the electrode plate may fall off and crack during processing or use due to the insufficient bonding strength. In detail:

[0051] By using the above binder combination, an inorganic substance with a second characteristic group, i.e., a sulfonate group (-SO3 - ) group as the bonding active site, and the polymer with the first characteristic group, that is, the sulfonate group (-SO3 - ) groups to form physical crosslinking points, that is, the first binder and the second binder can interact with each other through the sulfonate groups to form physical crosslinking points, which can alleviate the problem of low bonding strength between electrolytes such as sulfide solid electrolytes and non- / weakly polar binders, improve the bonding between the components in the electrode plate, and improve the mechanical strength of the electrode film layer. In addition, using inorganic substances with the second characteristic group as bonding active sites can improve the dispersibility of the binder combination and the conductive agent, and can also improve the electronic conductivity, forming a more effective conductive network, which is beneficial to improving the rate performance of the electrode plate, and then to improving the reliability and electrochemical performance of the battery containing the electrode plate.

[0052] It should be understood that the above-mentioned physical crosslinking points refer to the connection points formed between polymer chains by non-chemical bonding, which do not involve the formation of covalent bonds, but are achieved by physical forces. The first binder and the second binder are both sulfonated materials, and the physical forces involved in the sulfonated materials are ionic interactions, and the charged functional groups form physical crosslinking points through electrostatic effects.

[0053] Thus, the provided binder combination contains a small amount of characteristic group sulfonate (-SO3 - ) group, the sulfonate group (-SO3 - ) groups can not only form ionic bonds with metal ions, but also ion pairs with sulfonate (-SO3 - ) groups (such as -SO3 - M +The physical cross-linking caused by the ionic micro-regions improves the bonding performance of the binder combination, effectively alleviating the problem of weak interaction between the existing non-polar or weakly polar materials and other components of the electrode plate, resulting in insufficient bonding strength. In addition, the improvement of bonding performance can improve the mechanical strength of the electrode plate and improve the related performance of the solid-state battery, such as electrochemical performance such as cycle performance.

[0054] Using the adhesive combination provided in the embodiments of the present application in a battery, such as in the electrode plates of a solid-state battery, can improve the bonding performance of the electrode plates, effectively alleviate the powder loss and cracking of the electrode plates during processing or use, and thus help improve the overall performance and reliability of the battery.

[0055] The inventors have found through in-depth research that when the adhesive combination of the present application satisfies the above-mentioned design conditions and optionally satisfies one or more of the following conditions, the performance of the adhesive combination can be further improved.

[0056] In some embodiments, the polymer with the first characteristic group comprises a sulfonated polymer.

[0057] In some embodiments, in the first binder, the first characteristic group includes a terminal group -SO3M (ie, -SO3 - M + ), wherein M includes a metal element. For example, the M element may be an alkali metal element, an alkaline earth metal element, or the like.

[0058] In some embodiments, M includes, but is not limited to, any one or more combinations of Li (lithium), Na (sodium), Mg (magnesium), Al (aluminum), Ca (calcium), K (potassium), Pd (palladium) or Ba (barium).

[0059] In the present application, the polymer with the first characteristic group can be selected from sulfonated polymers, that is, the polymer with the first characteristic group can be obtained by sulfonating the polymer. The first characteristic group can be a terminal group -SO3M, and M can be one or more metal elements such as Li, Na, Mg, Al, Ca, K, Pd, and Ba.

[0060] Therefore, by including the M element, i.e., the metal element, in the first characteristic group, the chemical stability of the binder and the electrolyte can be improved. In addition, after ionization, i.e., after the introduction of the M element, a certain degree of ion conduction can be achieved, which can reduce the influence of the polymer on ion conduction.

[0061] In some embodiments, the polymer with the first characteristic group may be a sulfonated polymer, which may be obtained by sulfonating the polymer, wherein the polymer may be selected from styrene thermoplastic elastomers, etc. As an example, the polymer includes, but is not limited to, at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyether sulfone, polyether ketone, polyarylether, polyimide, polyester, ethylene propylene rubber, butyl rubber, fluororubber, styrene butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polystyrene-poly (ethylene-butylene)-polystyrene block copolymer (SEBS) or polystyrene-polybutadiene-polystyrene triblock copolymer (SBS) and other styrene thermoplastic elastomers. It should be understood that the polymer may be any one of the above substances, or may be a mixture of any two or more of the above substances, which are not listed here one by one.

[0062] Therefore, the polymer with the first characteristic group can be obtained by sulfonating a polymer such as polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyether sulfone, polyether ketone, polyarylether, polyimide, polyester, etc.

[0063] It should be noted that the polymer is not limited to the above-mentioned substances, and can be used for sulfonation and have a certain adhesiveness, which does not limit the purpose of the present invention. Other similar polymers can also be used in the present invention.

[0064] In some embodiments, the degree of sulfonation of the polymer with the first characteristic group, i.e., the sulfonated polymer, is 0.01 to 1 mol / kg. Preferably, in some embodiments, the degree of sulfonation of the sulfonated polymer is 0.1 to 0.5 mol / kg. As an example, the degree of sulfonation of the sulfonated polymer is 0.01 mol / kg, 0.02 mol / kg, 0.05 mol / kg, 0.1 mol / kg, 0.15 mol / kg, 0.2 mol / kg, 0.3 mol / kg, 0.4 mol / kg, 0.45 mol / kg, 0.5 mol / kg, 0.6 mol / kg, 0.8 mol / kg, 1 mol / kg, etc., or within the range of any two of the above values.

[0065] By controlling the sulfonation degree of the sulfonated polymer within the above range, it is possible to maintain good adhesion and mechanical properties while also having better solubility, better dispersibility, better chemical stability and other properties.

[0066] It should be noted that the preparation of the above-mentioned sulfonated polymer can be carried out by a conventional sulfonating agent method, which is not limited in the present embodiment. As an example, one feasible method for preparing the above-mentioned sulfonated polymer includes:

[0067] The polymer is first dissolved in an organic solvent, and then concentrated sulfuric acid and acetic anhydride are added in batches as sulfonating agents; after a certain reaction time, ethanol is added to terminate the reaction; then, it is neutralized with an ethanol aqueous solution of a metal acetate; the solvent is then removed with boiling water, and after washing with water and ethanol, vacuum drying is performed to obtain a sulfonated polymer.

[0068] The metal element in the metal acetate includes the above-mentioned M element. That is, the M ions in the sulfonated polymer are introduced by the metal acetate, such as the introduction of Li ions by adding lithium acetate. During the preparation of the sulfonated polymer, the metal acetate is added to neutralize the H + , improve the chemical stability with the electrolyte. In addition, it can also achieve a certain degree of ion conduction after ionization, which can reduce the influence of the polymer on ion conduction.

[0069] In some embodiments, the inorganic substance with the second characteristic group, ie, the sulfonated inorganic substance, comprises a sulfonated carbon material. Optionally, the carbon material can be selected from carbon materials with high electronic conductivity.

[0070] Therefore, adding sulfonated carbon material to the binder combination can not only serve as bonding active sites to improve the bonding properties of the binder combination, but also has a certain conductivity and can provide a certain electronic conductivity to form a more effective conductive network and improve conductivity.

[0071] In some embodiments, the inorganic substance with the second characteristic group, such as the sulfonated carbon material, includes, but is not limited to, at least one of sulfonated graphite, sulfonated graphene, sulfonated carbon nanotubes, or sulfonated carbon fibers. It should be understood that the sulfonated carbon material can be any one of the above substances, or can be a mixture of any two or more of the above substances, and will not be listed one by one here.

[0072] The sulfonated carbon material can be obtained by sulfonating a carbon material having high electronic conductivity, such as graphite, graphene, carbon nanotubes, and carbon fibers.

[0073] It should be noted that the above-mentioned carbon materials are not limited to the substances listed above, and can be used for sulfonation and have a certain electronic conductivity, which does not limit the purpose of the present invention. Other similar carbon materials can also be used in the present invention.

[0074] It should also be noted that the preparation of the above-mentioned sulfonated carbon material can be prepared by a conventional sulfonation method, which is not limited in the present embodiment. As an example, one feasible method for preparing the above-mentioned sulfonated carbon material includes:

[0075] Sulfonated graphene is prepared by using p-aminobenzenesulfonic acid as the sulfonating agent through pre-reduction, sulfonation, glucose secondary reduction and other reaction processes. In addition, commonly used sulfonating reagents include 4-diazobenzenesulfonate, chlorosulfonic acid, sulfuric acid and 2-chloroethanesulfonic acid. The sulfonation methods of other carbon materials are similar. After sulfonation with the sulfonating reagent, the sulfonated carbon material is washed with deionized water to neutrality.

[0076] In some embodiments, the mass ratio of the first binder to the second binder is (80-99):(1-20). As an example, the mass ratio of the first binder to the second binder can be 80:20, 85:15, 90:10, 95:5, 99:1, etc.

[0077] In the present application, the content of the first binder is greater than that of the second binder. In particular, by controlling the mass ratio of the first binder to the second binder within the above range, it is possible to ensure the bonding effect while also improving other properties such as conductivity and dispersibility.

[0078] In the present application, the preparation of the adhesive combination may include: preparing a first adhesive and a second adhesive separately, and mixing the first adhesive and the second adhesive in proportion to obtain the adhesive combination.

[0079] [Electrode Plate]

[0080] In some embodiments, the present application provides an electrode plate, the electrode plate comprising:

[0081] current collector;

[0082] The electrode film layer is arranged on at least one side surface of the current collector along the thickness direction; the electrode film layer includes the above-mentioned binder combination.

[0083] In the present application, the electrode plate includes a current collector and an electrode film layer disposed on at least one side surface of the current collector; wherein the electrode film layer includes an active material, a solid electrolyte, a conductive agent and the aforementioned binder combination.

[0084] Based on the same inventive concept, an embodiment of the present application also provides an electrode plate, which includes the above-mentioned adhesive combination. It should be understood that since the electrode plate includes the above-mentioned adhesive combination, all the features and advantages described in the previous text for the "adhesive combination" are also applicable to the "electrode plate" and will not be repeated here one by one.

[0085] The above “the electrode film layer is disposed on at least one side surface of the current collector along the thickness direction” means that the electrode film layer can be disposed on one surface of the current collector along its own thickness direction, or on two surfaces of the current collector along its own thickness direction. The “surface” here can be the entire area of ​​the current collector or a partial area of ​​the current collector. This application has no particular limitation on this, as long as the purpose of this application can be achieved.

[0086] As an example, the current collector has two surfaces opposite to each other in its thickness direction, and the electrode film layer is disposed on the two opposite surfaces of the current collector. It is understood that in other embodiments, the electrode film layer can also be stacked on any one of the two surfaces of the current collector.

[0087] In some embodiments, the electrode plate may be a positive electrode plate or a negative electrode plate.

[0088] The binder combination provided in the present application can be applied to a positive electrode sheet or a negative electrode sheet. Preferably, the electrode film layer in the positive electrode sheet or the negative electrode sheet contains a solid electrolyte, so that by adding the provided binder combination, the bonding problem between the binder and the solid electrolyte in the electrode film layer of the electrode sheet, or the interaction problem between the binder and other components in the electrode film layer can be alleviated.

[0089] In some embodiments, in the electrode film layer, the solid electrolyte includes a sulfide electrolyte.

[0090] In some embodiments, the sulfide electrolyte includes, but is not limited to, LGPS (Li 10 GeP2S 12 )、LSPS(Li 10 SnP2S 12 ), LPS (Li2S-P2S5) or Li6PS5X, or any one or a combination of two or more thereof; wherein X is selected from at least one of Cl, Br or I.

[0091] The above-mentioned sulfide electrolyte can be used in the positive electrode sheet or the negative electrode sheet. That is, when the electrode sheet is a positive electrode sheet, the solid electrolyte in the electrode film layer can adopt the above-mentioned sulfide electrolyte. When the electrode sheet is a negative electrode sheet, the solid electrolyte in the electrode film layer can also adopt the above-mentioned sulfide electrolyte.

[0092] It should be understood that in the electrode pole piece comprising active materials, solid electrolytes, binders and conductive agents, conventional binders in the prior art mainly provide bonding force through polar groups, and sulfide electrolytes are unstable with polar groups (easily chemically reacted), therefore, the bonding effect of conventional binders is poor. The binder composition provided in the embodiment of the present application can be mainly used to alleviate the problem of bonding strength of existing sulfide electrolytes. Therefore, the solid electrolyte in the above-mentioned electrode film layer can be mainly selected from sulfide solid electrolytes. Of course, it is not limited to this, and other types of solid electrolytes can also be used in combination with the binder of the present application, such as, by adding the binder combination provided in the present application, the effect of further improving the bonding strength can be achieved.

[0093] By adding solid electrolytes to the electrode film layer of the electrode plate, it can provide an ion transmission channel, that is, the addition of solid electrolyte materials to the electrode plate can enhance the transmission of active ions such as lithium ions in the electrode plate.

[0094] In some embodiments, when the electrode plate is a positive electrode plate, the active material is a positive electrode active material, for example, the active material may include, but is not limited to, at least one of a lithium-containing transition metal oxide (lithium-containing transition metal composite oxide) containing a nano-coating layer, a lithium-containing transition metal sulfide, elemental sulfur or a sulfur-carbon mixture.

[0095] As an example, in the positive electrode plate, the active material may include a base material and a nano-coating layer coated on the surface of the base material; for example, the active material includes at least one of LMO (lithium manganese oxide), LCO (lithium cobalt oxide), NMC (lithium nickel manganese cobalt oxide), NCA (lithium nickel cobalt aluminum oxide), LNCO (lithium nickel cobalt oxide), olivine compounds (LiMePO4, Me = one or more of Fe, Co, Ni, Mn) containing a nano-coating layer, and transition metal composite oxides containing lithium, elemental sulfur, and sulfur-carbon mixtures.

[0096] Optionally, in the positive electrode plate, the material of the nano-coating layer is selected from any one or a combination of two or more of Li3PO4, Al2O3, LiNbO3, LiAlO2, Li3BO3, Li2OZrO2, MgO, HfO2, Li2SiO3, B2O3, Li2O, Nb2O5, P2O5, SiO2, Sc2O3, TiO2 or ZrO2.

[0097] Optionally, in the positive electrode sheet, the conductive agent is preferably a conductive carbon material, which includes, but is not limited to, at least one of conductive carbon black (Super P), conductive graphite, vapor-grown carbon fiber (VGCF), carbon nanotubes, or conductive graphene. Among them, the conductive carbon black may include acetylene black, Ketjen black, etc.

[0098] The conductive agent in the positive electrode plate can be any of various conductive carbon materials known in the art that can be used in batteries. It is not limited to the above-mentioned carbon materials, and other types can also be used, which is not limited to this.

[0099] Optionally, in the positive electrode sheet, the mass ratio of the active material, the solid electrolyte, the conductive agent and the binder is (50-90): (10-30): (1-5): (1-10).

[0100] In the electrode film layer of the above-mentioned positive electrode sheet, the mass proportion of active material can be 50% to 90%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% and the like; the mass proportion of solid electrolyte can be 10% to 30%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% and the like. The mass proportion of the conductive agent can be 1% to 5%, for example, 1%, 2%, 3%, 4%, 5%, etc.; the mass proportion of the adhesive combination can be 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0101] As an improvement of the electrode plate of the present application, such as the positive electrode plate, the current collector can be a foil commonly used in batteries. For example, the current collector can be aluminum foil, copper foil, nickel foil, titanium foil, stainless steel foil, etc., or the above metal foil with a carbon coating layer. Preferably, the current collector can be one of aluminum foil and carbon-coated aluminum foil.

[0102] In some embodiments, when the electrode plate is a negative electrode plate, the active material is a negative electrode active material, such as, the active material includes a carbon-based material and / or a silicon-based material, that is, the active material can be a carbon-based material, can be a silicon-based material, or can be a combination of a carbon-based material and a silicon-based material.

[0103] As an example, in the negative electrode plate, the active material includes, but is not limited to, any one of graphite, silicon, silicon oxide, silicon carbon, graphene, soft carbon, and hard carbon, or a combination of two or more thereof.

[0104] The active material in the negative electrode plate can be any known negative electrode active material applicable to batteries in the art, but is not limited to the above-mentioned negative electrode active materials. Other types can also be used, which is not limited to this.

[0105] In some embodiments, in the negative electrode plate, the conductive agent is preferably a conductive carbon material, which includes, but is not limited to, at least one of conductive carbon black (Super P), conductive graphite, vapor-grown carbon fiber (VGCF), carbon nanotubes, or conductive graphene. Among them, the conductive carbon black may include acetylene black, Ketjen black, etc.

[0106] The conductive agent in the negative electrode plate can be any of various conductive carbon materials known in the art that can be used in batteries. It is not limited to the above-mentioned carbon materials, and other types can also be used, which is not limited to this.

[0107] Optionally, in the negative electrode sheet, the mass ratio of the active material, the solid electrolyte, the conductive agent and the binder is (50-90): (10-30): (1-5): (1-10).

[0108] In the electrode film layer of the above-mentioned negative electrode sheet, the mass proportion of active material can be 50% to 90%, for example, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% and the like; the mass proportion of solid electrolyte can be 10% to 30%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% and the like. The mass proportion of the conductive agent can be 1% to 5%, for example, 1%, 2%, 3%, 4%, 5%, etc.; the mass proportion of the adhesive combination can be 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0109] As an improvement of the electrode plate of the present application, such as the negative electrode plate, the current collector can be a foil commonly used in batteries. For example, the current collector can be aluminum foil, copper foil, nickel foil, titanium foil, stainless steel foil, etc., or the above metal foil with a carbon coating layer. Preferably, the current collector can be one of copper foil, carbon-coated copper foil, and stainless steel foil.

[0110] In some embodiments, a method for preparing an electrode sheet includes:

[0111] The binder combination is mixed with a solvent to obtain a glue solution, and then the glue solution is mixed with an active material, a solid electrolyte, and a conductive agent to obtain a pole piece slurry. The pole piece slurry is coated on a current collector, and after heating and drying, an electrode pole piece is obtained.

[0112] In some embodiments, the solvent includes, but is not limited to, aliphatic hydrocarbons, aromatic hydrocarbons, esters, ethers, and alcohol solvents.

[0113] As an example, in the process of preparing electrode plates, the solvent used for mixing with the binder combination may include aliphatic hydrocarbon solvents such as pentane, hexane, 2-ethylhexane, heptane, octane, decane, undecane, dodecane, and tridecane; cycloalkane solvents such as cyclohexane and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, p-xylene, mesitylene, ethylbenzene, and tert-butylbenzene; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, and benzyl acetate; ether solvents such as dibutyl ether, diamyl ether, anisole, diethylene glycol diethyl ether, and cyclopentyl methyl ether; and alcohol solvents such as methanol, ethanol, isopropanol, and benzyl alcohol.

[0114] In some embodiments, the drying heating temperature is 60-100° C., and the drying time is 10-20 hours.

[0115] [Solid-state battery]

[0116] In some embodiments, the present application provides a solid-state battery, which includes an electrode plate as described above.

[0117] Optionally, the solid-state battery can be an all-solid-state battery or a semi-solid-state battery, preferably an all-solid-state battery.

[0118] In some embodiments, the solid-state battery includes a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, and the solid electrolyte layer is arranged between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet and the negative electrode sheet can be the electrode sheet provided in the embodiment of the present application.

[0119] In some embodiments, in a solid-state battery, the solid electrolyte in the solid electrolyte layer may be one or more of various solid electrolyte materials known in the art, such as a halide electrolyte, a sulfide electrolyte, an oxide electrolyte, a polymer electrolyte, and the like.

[0120] Since the solid-state battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0121] In the embodiment of the present invention, the battery can be wound or laminated according to the actual situation, and the manufacturing method is not limited.

[0122] The shape of the outer casing of the battery is also arbitrary, and may be, for example, cylindrical, square, laminated, button-shaped, or the like.

[0123] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.

[0124] Example 1

[0125] 1. Preparation of positive electrode sheet

[0126] 0.130 g of sulfonated ethylene-propylene rubber, 0.013 g of sulfonated graphene, and 7.066 g of p-xylene solvent were mixed to obtain a rubber solution, wherein the sulfonation degree of the ethylene-propylene rubber was 0.1 mol / kg;

[0127] The prepared glue was then mixed with 6.933 g of positive electrode active material NCM811, 1.387 g of sulfide electrolyte LPSCl, and 0.173 g of conductive agent VGCF to obtain a pole piece slurry, the pole piece slurry was coated on an aluminum foil, and heated and dried at 60° C. to obtain a positive electrode piece.

[0128] 2. Preparation of negative electrode sheet

[0129] 0.080 g of sulfonated ethylene-propylene rubber, 0.008 g of sulfonated graphene, and 5.316 g of p-xylene solvent were mixed to obtain a rubber solution, wherein the sulfonation degree of the ethylene-propylene rubber was 0.1 mol / kg;

[0130] The prepared glue was then mixed with 3.788 g of negative electrode active material graphite, 1.334 g of sulfide electrolyte LPSCl, and 0.107 g of conductive agent VGCF to obtain electrode slurry, the electrode slurry was coated on a stainless steel foil, and heated and dried at 60° C. to obtain a negative electrode.

[0131] Example 2

[0132] Embodiment 2 is substantially the same as Embodiment 1, except that:

[0133] The sulfonation degree of the ethylene propylene rubber in the positive electrode sheet and the negative electrode sheet is 0.3 mol / kg.

[0134] The rest are the same as in Example 1.

[0135] Example 3

[0136] Embodiment 3 is substantially the same as Embodiment 1, except that:

[0137] The sulfonation degree of the ethylene propylene rubber in the positive electrode sheet and the negative electrode sheet is 0.5 mol / kg.

[0138] The rest are the same as in Example 1.

[0139] Example 4

[0140] Embodiment 4 is substantially the same as Embodiment 1, except that:

[0141] The sulfonated EPDM was replaced by sulfonated polyvinylidene fluoride.

[0142] The rest are the same as in Example 1.

[0143] Example 5

[0144] Embodiment 5 is substantially the same as Embodiment 1, except that:

[0145] The sulfonated EPDM was replaced by sulfonated polyimide.

[0146] The rest are the same as in Example 1.

[0147] Example 6

[0148] Embodiment 6 is substantially the same as Embodiment 1, except that:

[0149] The sulfonated graphene was replaced by sulfonated graphite.

[0150] The rest are the same as in Example 1.

[0151] Example 7

[0152] Embodiment 7 is substantially the same as Embodiment 1, except that:

[0153] The sulfonated graphene was replaced by sulfonated carbon nanotubes.

[0154] The rest are the same as in Example 1.

[0155] Example 8

[0156] Embodiment 8 is substantially the same as Embodiment 1, except that:

[0157] In the preparation of the positive electrode sheet, 0.130 g of sulfonated ethylene propylene rubber, 0.026 g of sulfonated graphene, and 7.076 g of p-xylene solvent were mixed to obtain a glue solution;

[0158] In the preparation of the negative electrode sheet, 0.080 g of sulfonated ethylene propylene rubber, 0.016 g of sulfonated graphene, and 5.324 g of p-xylene solvent were mixed to obtain a glue solution.

[0159] The rest are the same as in Example 1.

[0160] Example 9

[0161] Embodiment 9 is substantially the same as Embodiment 1, except that:

[0162] In the preparation of the positive electrode sheet, 0.130 g of sulfonated ethylene propylene rubber, 0.001 g of sulfonated graphene, and 7.056 g of p-xylene solvent were mixed to obtain a glue solution;

[0163] In the preparation of the negative electrode sheet, 0.080 g of sulfonated ethylene propylene rubber, 0.001 g of sulfonated graphene, and 5.309 g of p-xylene solvent were mixed to obtain a glue solution.

[0164] The rest are the same as in Example 1.

[0165] Example 10

[0166] Embodiment 10 is substantially the same as Embodiment 1, except that:

[0167] In the preparation of the positive electrode sheet, the prepared glue was mixed with 6.933 g of positive electrode active material NCM811, 1.733 g of sulfide electrolyte LPSCl, and 0.173 g of conductive agent VGCF to obtain a plate slurry.

[0168] The rest are the same as in Example 1.

[0169] Embodiment 11

[0170] Embodiment 11 is substantially the same as Embodiment 1, except that:

[0171] In the preparation of the negative electrode sheet, the prepared glue was mixed with 3.788 g of negative electrode active material graphite, 1.601 g of sulfide electrolyte LPSCl, and 0.107 g of conductive agent VGCF to obtain a plate slurry.

[0172] The rest are the same as in Example 1.

[0173] Comparative Example 1

[0174] Comparative Example 1 is substantially the same as Example 1, except that:

[0175] In the preparation of positive and negative electrodes,

[0176] Replace sulfonated EPDM with unsulfonated EPDM,

[0177] The sulfonated graphene was replaced with unsulfonated graphene.

[0178] The difference between Comparative Example 1 and Example 1 mainly lies in the use of unsulfonated polymer and unsulfonated carbon material.

[0179] Comparative Example 2

[0180] Comparative Example 2 is substantially the same as Example 1, except that:

[0181] In the preparation of the positive electrode sheet and the negative electrode sheet, sulfonated graphene is omitted.

[0182] The main difference between Comparative Example 2 and Example 1 is that no second binder is added.

[0183] Performance Testing

[0184] 1. The positive electrode sheets and negative electrode sheets obtained in the above embodiments and comparative examples are subjected to performance tests, specifically including:

[0185] Peel strength testing, including:

[0186] 1) Sample preparation: pole piece stripping; size: 19mm*400mm;

[0187] 2) Fixation: stick the double-sided tape on the electrode surface and the other side on the stainless steel plate;

[0188] 3) Test: Fix the stainless steel plate and the current collector on the two fixtures of the electronic tensile testing machine, and then perform a 180-degree peel test at a speed of 100 mm / min; when the electrode current collector and the electrode film layer are completely separated, read the test results of the peel strength, and take the average value of the stable stage as the peel strength value;

[0189] 4) Test results: The results are based on the average peel force in the length direction, and the unit is N / cm.

[0190] The test results are shown in Table 1.

[0191] 2. Assemble the positive electrode sheets and negative electrode sheets obtained in the above embodiments and comparative examples into a battery. Specifically:

[0192] Take 8 mg of solid electrolyte, put it into the tablet press mold, apply 300 MPa pressure, and obtain a solid electrolyte sheet with a diameter of Φ10 mm and a thickness of 60 um;

[0193] The positive electrode sheet and negative electrode sheet with a diameter of Φ10mm are cut by a slicer, and the positive electrode sheet, solid electrolyte sheet and negative electrode sheet are placed in the battery mold in sequence. Then, a pressure of 100MPa is applied to the metal pole of the battery mold and the bolts are tightened to obtain a solid-state battery.

[0194] The assembled solid-state battery is then subjected to electrochemical performance tests, including:

[0195] 1) Cycle test: The electrochemical performance of the assembled battery was tested using a battery test system (Land, CT2001A). Constant current charge and discharge tests were performed at a temperature of 60°C within a voltage range of 3.0V–4.2V with a cycle rate of 1C.

[0196] 2) Rate test: The charge and discharge test was performed at a rate of 1C within the voltage range using an electrochemical test system (Land, CT2001A). The first cycle rate was 0.1C.

[0197] The test results are shown in Table 2 below.

[0198] Table 1 Test results of positive and negative electrodes in various embodiments and comparative examples

[0199]

[0200]

[0201] It can be seen from Table 1 that compared with comparative examples 1-2, the positive electrode sheets and negative electrode sheets prepared in embodiments 1-11 of the present invention have higher peel strength, indicating that the electrode sheets provided in the embodiments of the present invention have better bonding performance.

[0202] Table 2 Electrochemical performance test of solid-state batteries prepared in various embodiments and comparative examples

[0203]

[0204]

[0205] It can be seen from Table 2 that, compared with Comparative Examples 1-2, the solid-state batteries prepared using the positive electrode sheets and negative electrode sheets of Examples 1-11 of the present invention have better rate performance and capacity retention rate during the charge and discharge process, and improve the cycle performance and rate performance of the battery.

[0206] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0207] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0208] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0209] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0210] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A binder combination, characterized in that: The binder combination comprises: a first binder, the first binder comprising a polymer having a first characteristic group; and A second binder, wherein the second binder includes an inorganic substance having a second characteristic group; Wherein, the first characteristic group and the second characteristic group respectively include a sulfonate group.

2. The adhesive combination according to claim 1, characterized in that: The polymer with the first characteristic group comprises a sulfonated polymer; And / or, the first characteristic group includes a terminal group -SO3M, wherein the M includes a metal element.

3. The adhesive combination according to claim 2, characterized in that: The M includes at least one of Li, Na, Mg, Al, Ca, K, Pd or Ba; And / or, the sulfonation degree of the sulfonated polymer is 0.01 to 1 mol / kg.

4. The adhesive combination according to any one of claims 1 to 3, characterized in that: The polymer in the polymer with the first characteristic group includes at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyether sulfone, polyether ketone, polyarylether, polyimide, polyester, ethylene propylene rubber, butyl rubber, fluororubber, styrene butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polystyrene-poly (ethylene-butylene)-polystyrene block copolymer or polystyrene-polybutadiene-polystyrene triblock copolymer.

5. The adhesive combination according to any one of claims 1 to 3, characterized in that: The inorganic substance with the second characteristic group includes a sulfonated carbon material.

6. The adhesive combination according to claim 5, characterized in that: The sulfonated carbon material includes at least one of sulfonated graphite, sulfonated graphene, sulfonated carbon nanotubes or sulfonated carbon fibers.

7. The adhesive combination according to any one of claims 1 to 3, characterized in that: The mass ratio of the first binder to the second binder is (80-99):(1-20).

8. An electrode plate, characterized in that: The electrode plate comprises a current collector and an electrode film layer arranged on the surface of the current collector; The electrode film layer comprises an active material, a solid electrolyte, a conductive agent and a binder combination as claimed in any one of claims 1 to 7.

9. The electrode plate according to claim 8, characterized in that: The solid electrolyte includes a sulfide electrolyte; And / or, the electrode plate is a positive electrode plate, and the active material includes at least one of a lithium-containing transition metal oxide containing a nano-coating layer, a lithium-containing transition metal sulfide, elemental sulfur, or a sulfur-carbon mixture; And / or, the electrode plate is a negative electrode plate, and the active material includes a carbon-based material and / or a silicon-based material; and / or, the conductive agent comprises at least one of conductive graphite, conductive carbon black, vapor-grown carbon fiber, carbon nanotubes or conductive graphene; And / or, the mass ratio of the active material, solid electrolyte, conductive agent and binder is (50-90): (10-30): (1-5): (1-10).

10. A solid-state battery, characterized in that: The solid-state battery comprises the electrode plate according to any one of claims 8 to 9.